The effects of oil on As(V) adsorption on illite, kaolinite, montmorillonite and chlorite - Wainipee,W; Cuadros,J; Sephton,MA; Unsworth,C; Gill,MG; Strekopytov,S; Weiss,DJ (Geochimica et Cosmochimica Acta, 2013)
The effect of oil on As(V) adsorption on clay minerals has been investigated using batch experiments at low and high pH, NaCl concentration and oil contents. Four clay minerals were chosen because of their abundance in sediments and their different crystal chemistry: illite, kaolinite, montmorillonite, and chlorite. The values for pH were 4 and 8 and salt concentrations were 0.001 and 0.7 M NaCl to appreciate the effects of changing salinity, e.g from fresh water to seawater conditions. For the coating experiments, a well-characterised oil was used to survey the main effects of complex organic mixtures on adsorption and oil to clay mineral (w/w) ratios were 0.0325 and 0.3250. As(V) adsorption increased with increasing NaCl concentration, suggesting that the mechanisms of As(V) adsorption are related to the formation of inner-sphere complexes in which Na+ ions act as bridges between the clay surface and the As(V) anions. Cation bridging is also indicated by zeta potential measurements which show that higher NaCl concentrations along with the presence of As(V) can cause the clay particles and adsorbed ions to have a more negative overall charge. Adsorption is lower at higher pH due to the reduced number of positively charged sites on the edge of clay mineral layers. Oil coating reduces As(V) adsorption by decreasing the available surface area of clay minerals, except in the case of oil-coated montmorillonite, where surface area following dispersion in water is increased. The main variables controlling As(V) adsorption are surface area and surface charge density, as confirmed by a simplified quantitative model. These findings advance our ability to predict the effects of complex pollution events in various freshwater and marine settings.